2020
DOI: 10.1097/sap.0000000000002604
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Comprehensive Cleft Care Delivery

Abstract: Introduction We analyzed the perceptions of participants and faculty members in simulation-based comprehensive cleft care workshops regarding comprehensive cleft care delivery in developing countries. Methods Data were collected from participants and faculty members in 2 simulation-based comprehensive cleft care workshops organized by Global Smile Foundation. We collected demographic data and surveyed what they believed was the most significant barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We have previously evaluated the perceived barriers and limitations to comprehensive cleft care delivery among participants in this educational initiative and faculty. 7 Our analysis showed that the most significant barrier facing comprehensive cleft care delivery was financial limitations, which was concordant among faculty members and attendees. Similarly, the major intervention required to deliver comprehensive cleft care was creating multidisciplinary teams, also concordant between faculty members and attendees.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…We have previously evaluated the perceived barriers and limitations to comprehensive cleft care delivery among participants in this educational initiative and faculty. 7 Our analysis showed that the most significant barrier facing comprehensive cleft care delivery was financial limitations, which was concordant among faculty members and attendees. Similarly, the major intervention required to deliver comprehensive cleft care was creating multidisciplinary teams, also concordant between faculty members and attendees.…”
Section: Discussionmentioning
confidence: 57%
“…Faculty members included 25 (8.0%) surgeons, 5 (1.6%) dentists, 4 (1.3%) speech and language pathologists, and 6 (1.9%) from different specialties. 7 The total response rate was 57.8% (n ¼ 181), with the survey completed by 39 out of 40 faculty members (97.5%) and 142 out of 273 participants (52.0%). The majority of respondents were female (57.1%), 30 years or older (82.6%), and had more than 5 years of experience in their current position (69.5%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations